Implementing a finite-element time-domain program in parallel. - Malan, D.H (IEEE Antennas & propagation magazine.)
A number of issues relating to the implementation of a parallel finite-element program are discussed, including choice of programming language (principally FORTRAN90 versus C++), data-communication environment, matrix partitioner, and parallel preconditioner. Some results computed for an intricately shaped load in a microwave applicator are presented.